2010
DOI: 10.1002/masy.201000008
|View full text |Cite
|
Sign up to set email alerts
|

Loading of Bacterial Cellulose Aerogels with Bioactive Compounds by Antisolvent Precipitation with Supercritical Carbon Dioxide

Abstract: Bacterial cellulose aerogels overcome the drawback of shrinking during preparation by drying with supercritical CO2. Thus, the pore network of these gels is fully accessible. These materials can be fully rewetted to 100% of its initial water content, without collapsing of the structure due to surface tension of the rewetting solvent. This rehydration property and the high pore volume of these material rendered bacterial cellulose aerogels very interesting as controlled release matrices. Supercritical CO2 dryin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 24 publications
3
38
0
1
Order By: Relevance
“…However, it does not always confirm that the CNF aerogel follows the Korsmeyer-Peppas model. Literature mentions that the release from the CNFs depends on the thickness of the film/aerogel 22 and also on the property of the drug and the type of cellulose used in the formulation. …”
Section: Study Of Release Kineticsmentioning
confidence: 99%
“…However, it does not always confirm that the CNF aerogel follows the Korsmeyer-Peppas model. Literature mentions that the release from the CNFs depends on the thickness of the film/aerogel 22 and also on the property of the drug and the type of cellulose used in the formulation. …”
Section: Study Of Release Kineticsmentioning
confidence: 99%
“…Beyond that, good biocompatibility and low immunogenic potential (Helenius et al, 2006; Klemm, Schumann, Udhardt, & Marsch, 2001) render BC a promising material for various biomedical applications. This comprises their use as artificial blood vessels (Klemm et al, 2001), semi-permanent artificial skin (Petersen & Gatenholm, 2011), as well as matrices for slow-release applications (Haimer et al, 2010), nerve surgery (Klemm et al, 2001), engineering of bone tissue (Zaborowska et al, 2010) or artificial knee menisci (Bodin, Concaro, Brittberg, & Gatenholm, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Liebner et al (2007Liebner et al ( , 2008 have reported the cellulose aerogels produced by scCO 2 drying of regenerated cellulose obtained by solvent exchange of a solution of cellulose in N-methylmorpholine-N-oxide; these materials showed surface areas of 172-284 m 2 /g. In another study, cellulose aerogels have been prepared by scCO 2 drying of the bacterial cellulose produced by the gram-negative bacterium Gluconacetobacter xylinum, resulting in highly porous dry cellulose aerogels showing a density of 8 mg/cm 3 (Figures 5 and 6;Haimer et al 2010, Liebner et al 2010. Cellulose gels have been dried in scCO 2 followed by calcination and subsequent doping by platinum nanoparticles, yielding nanostructured highly porous electrocatalysts used for oxygen reduction (Guilminot et al 2008).…”
Section: Porous Materialsmentioning
confidence: 99%